EFFECTS OF SEX EDUCATION AMONG PRIVATE SECONDARY SCHOOL GIRLS IN ILEKUN COMMUNITY, AKURE SOUTH LOCAL GOVERNMENT AREA, ONDO STATE, NIGERIA - Ilegbusi, Paul; TOMORI, MICHAEL (My University, 2024)
Sexuality education is a central aspect of being human throughout life and encompasses sex, gender identities and roles, sexual orientation, eroticism, pleasure, intimacy and reproduction. This study was aimed at investigating the effects of sex education among private secondary school girls in Ilekun, Akure South Local Government Area, Ondo State, Nigeria. The study design was descriptive, using simple random technique and 120 structured questionnaires were administered and retrieved for analysis, using SPSS frequency table and simple percentage. The study revealed that 97.5% of the students have heard about sex education, comprising 39% (from home), 28% (from school), 11.6% (from religious houses), 5.8% (from internet), 4% (from friends), 3% (from radio/television), 2.5% (from social media), and 2.5% (from sexual books/magazines). Those introduced to sex education between 10 and 14 years old were 65.8%; 51.6% agreed that sex education is not taught in secondary schools because of the following reasons: shy to talk about it (82.5%), not included in school curriculum (82.5%), no trained sex education counselor (72.5%), and no enough time for it in school (76.6%). Effects of sex education include: reduction of unwanted pregnancy (90.8%), reduced sexually transmitted infections (93%), changes one’s sexual attitude (91.6%), being responsible (87.5%), promotes abstinence (79%), and lacks of it leads to rape (94%). The study concludes that sex education should be integrated into the secondary school curriculum with well trained counselors. Additionally, it emphasizes the role of parents, religious institutions, communities and government in promoting sexuality education.
N/A
This is an international scientific conference research paper presentation on the effects of sex education among private secondary school girls.
Keywords: Education; Effects; Sex education; Sexuality